Surface profile measurement of 3D-printed transparent objects using nonlinear optics - Jiao, Jiannan (2018)
In Additive Manufacturing (AM), it is necessary to measure the surface profile of 3D-printed transparent objects in noninvasive manner, which remained, however, practically difficult to date. Nonlinear optical responses of transparent materials have been utilized in shortwavelength light generation, optical phase/intensity modulators, and non-destructive inspection of the sample characteristics. In this research, we introduced nonlinear optics to surface profile measurement of 3D-printed micro-optic structures. For in-depth understanding of third harmonic generation mechanisms, the harmonic conversion efficiency was measured with different input polarization states, incident angles, and focal depths in the transparent materials including Sapphire and Si wafers. Our results can be utilized in surface inspection required in various industrial and scientific applications, including 3D-profile measurement of printed optical components and waveguides.